2010
DOI: 10.1002/jms.1870
|View full text |Cite
|
Sign up to set email alerts
|

Observations of different core water cluster ions Y(H2O)n (Y = O2, HOx, NOx, COx) and magic number in atmospheric pressure negative corona discharge mass spectrometry

Abstract: Reliable mass spectrometry data from large water clusters Y(-)(H(2)O)(n) with various negative core ions Y(-) such as O(2)(-), HO(-), HO(2)(-), NO(2)(-), NO(3)(-), NO(3)(-)(HNO(3))(2), CO(3)(-) and HCO(4)(-) have been obtained using atmospheric pressure negative corona discharge mass spectrometry. All the core Y(-) ions observed were ionic species that play a central role in tropospheric ion chemistry. These mass spectra exhibited discontinuities in ion peak intensity at certain size clusters Y(-)(H(2)O)(m) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 55 publications
(83 reference statements)
1
31
0
Order By: Relevance
“…fingerprints, may get lost during the extraction and processing steps. Addressing these [21] Schilling et al, 2010 [12] 32 O 2…”
Section: Detection and Identification Of Cocaine On Banknotesmentioning
confidence: 96%
See 1 more Smart Citation
“…fingerprints, may get lost during the extraction and processing steps. Addressing these [21] Schilling et al, 2010 [12] 32 O 2…”
Section: Detection and Identification Of Cocaine On Banknotesmentioning
confidence: 96%
“…Sekimoto et al, 2011 [21] Schilling et al, 2010 [12] 44 SiO À Schilling et al, 2010 [12] 45 HCO 2 À Sekimoto et al, 2012 [33] 46 NO 2 À Sekimoto et al, 2011 [21] Schilling et al, 2010 [12] [21] drawbacks, several studies have shown that ambient ionization/desorption MS techniques may be an alternative method in sensing paper currency for controlled substances and drug money. [25,26] It has been shown that FAPA-MS is capable of ionizing and detecting trace amounts of organic compounds on a variety of substrates.…”
mentioning
confidence: 96%
“…e background spectrum (Fig. 2a) 11) although the source of the carbon atoms of CO x and HCO x ions has not been yet clari ed. e spectrum obtained in the presence of the HF supply (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…11) e corona discharge experiments for generating negative atmospheric core ions Y − (Y=O 2 , HO x , NO x , CO x ) 11,12) were performed under ambient laboratory conditions in the presence of nitrogen (N 2 ), oxygen (O 2 ), water vapors (H 2 O), and minor amounts of other species, such as CO 2 and Ar. e laboratory temperature and relative humidity were 298 K and 40-70%, respectively.…”
Section: Atmospheric Pressure Corona Discharge Ionizationmentioning
confidence: 99%
“…3e, and m/z 126 in Fig. 3f ) and water molecules in the atmospheric pressure dri region (10 5 Pa), the inside of the ori ce hole (≈10 5 Pa) and/or adiabatic expansion in the vacuum region (270 Pa), 17) as sown in Fig. 2.…”
Section: Mass Spectra Of Benzene and Its Derivatives By Positive-ion mentioning
confidence: 98%